University physics with modern physics - Bauer, W (McGraw-Hill, 2012)
Covers calculus, incorporating a consistently used 7-step problem solving method. This title includes various contemporary topics as well as research-based discussions. It shows how physics concepts are related to the development of the technologies in the fields of engineering, medicine, astronomy and more.